Penerapan Exercise Range Of Motion (ROM) Terhadap Intensitas Nyeri Pada Pasien Post Operasi Fraktur Ektermitas Di Rsud Pandan Arang Boyolali Di Ruang Binahong - Ingkang Wilujeng; Eska Dwi Prajayanti; Panggah Widodo (Termometer: Jurnal Ilmiah Ilmu Kesehatan dan Kedokteran, 2023)
Background: The World Health Organization (WHO) in 2019 stated that the incidence of fractures is increasing, it has been recorded that fractures have occurred in approximately 15 million people with a prevalence rate of 3.2%. Fractures in 2017 there were approximately 20 million people with a prevalence rate of 4.2% and in 2018 it increased to 21 million people with a prevalence rate of 3.8% due to traffic accidents. Fractures can cause physical and psychological disorders in a person so that they can cause pain. One way to deal with non-pharmacological pain is the Range Of Motion (ROM) technique. Objective: Knowing the results of implementing Exercise Range of Motion (ROM) in postoperative patients with extremity fractures on pain intensity. Method: This implementation method uses a descriptive method. Results: The results of the application showed that there was an effect of reducing pain intensity with the ROM technique in patients with postoperative extremity fractures. Conclusion: There was a decrease in the pain scale before and after the Range Of Motion technique was performed in postoperative patients with extremity fractures.